Case for diagnosis. Multinucleated cell angiohistiocytoma - Margarida Rato; Ana Filipe Monteiro; Joana Parente; João Aranha (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Multinucleate cell angiohistiocytoma is a rare idiopathic benign fibrohistiocytic and vascular proliferation usually presenting as multiple asymptomatic papules, red to violaceous in colour, primarily located on the extremities of middle-aged females. This entity is probably underdiagnosed due to the lack of recognition by clinicians and pathologists. We describe a patient with a multinucleate cell angiohistiocytoma of the face, a less frequent localization, in order to increase awareness of this entity and elucidate its clinical, histopathological, and immunohistochemistry features.